Novel carboxylic acid terminated silicon(IV) and zinc(II) phthalocyanine photosensitizers: Synthesis, photophysical and photochemical studies - Hisir, Arif; Kose, Gulsah Gumrukcu; Atmaca, Goknur Yasa; Erdogmus, Ali; Karaoglan, Gulnur Keser (WORLD SCI PUBL CO INC, 2018)
In order to improve the efficacy of photochemical properties for photodynamic therapy (PDT) applications, carboxylic acid groups axially conjugated with silicon(IV) and at the peripheral position with zinc(II) phthalocyanine skeletons for new photosensitizers to investigate the influence of the COOH group positions on the photophysicochemical performance are described in this study. Silicon (IV) (3 and 5) and zinc (II) (7) phthalocyanines were characterized by UV-vis, FTIR, H-1-NMR,MALDI-TOF MS and elemental analysis spectral data. Furthermore, the photophysical (fluorescence quantum yields and fluorescence quenching studies), photochemical (photodegradation and singlet oxygen generation) and aggregation properties of the newly synthesized phthalocyanines were investigated in dimeihylformamide (DMF) and dimethyl sulfoxide (DMSO) solutions. The results were compared with that of zinc and silicon phthalocyanines. Singlet oxygen quantum yields ranged from 0.23 to 0.63 via Type II mechanism under the experimental conditions studied. The fluorescence of the phthalocyanine complexes (3, 5 and 7) is effectively quenched by 1,4-benzoquinone (BQ) in DMSO, DMF and THF.
Keywords: phthalocyanine; axially; carboxylic acid; silicon; photochemistry; photophysical; PHOTODYNAMIC THERAPY; IN-VITRO; AGGREGATION BEHAVIORS; IRON PHTHALOCYANINE; SUBSTITUTED SILICON; IV PHTHALOCYANINES; ELECTRON-TRANSFER; CENTRAL METAL; GALLIUM III; WATER; Chemistry